Jorge Eduardo Rivera: philosophical and vital motivations. In search of a unifying background - Neumann Soto, Hardy (Anales del Seminario de Historia de la Filosofía, 2025)
This paper aims to identify a potential thematic core in the thought of Jorge Edo. Rivera, as it is manifested both explicitly and implicitly in his writings, particularly in his book De Asombros y Nostalgia. It is argued that this core is structured around a set of ideas centered on the notion of ‘executivity’. Moreover, it is crucial to address this challenge by not only focusing on the content of his work but also on the way in which his thoughts are presented. This is because in the works of the Chilean philosopher, the integration of both aspects is profound, and thus they also become a fundamental part of his philosophical discourse.